New Insights into the Diurnal Rhythmicity of Gut Microbiota and Its Crosstalk with Host Circadian Rhythm - Hongyu Wang; He Zhang; Yong Su (Animals, 2022)
Unlike the strictly hierarchical organization in the circadian clock system, the gut microbiota rhythmicity has a more complex multilayer network of all taxonomic levels of microbial taxa and their metabolites. However, it is worth noting that the functionality of the gut microbiota rhythmicity is highly dependent on the host circadian clock and host physiological status. Here, we discussed the diurnal rhythmicity of the gut microbiota; its crucial role in host physiology, health, and metabolism; and the crosstalk between the gut microbial rhythmicity and host circadian rhythm. This knowledge lays the foundation for the development of chronotherapies targeting the gut microbiota. However, the formation mechanism, its beneficial effects on the host of gut microbial rhythmicity, and the dynamic microbial–host crosstalk are not yet clear and warrant further research.